2000
DOI: 10.1007/s004250050044
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi apparatus of the scaly green flagellate Scherffelia dubia : uncoupling of glycoprotein and polysaccharide synthesis during flagellar regeneration

Abstract: The flagella of the green alga Scherffelia dubia are covered by scales which consist of acidic polysaccharides and glycoproteins. Experimental deflagellation results in the regeneration of flagella complete with scales. During flagellar regeneration, scales are newly synthesized in the Golgi apparatus, exocytosed and deposited on the growing flagella. Flagellar regeneration is dependent upon protein synthesis and N-glycosylation, as it is blocked by cycloheximide and partially inhibited by tunicamycin. Metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Scaleforming algae can serve as a "reality check" for models of Golgi traffic (Becker et al 1995). Figure 6A shows a thin-section electron micrograph of S. dubia (Perasso et al 2000). Two Golgi stacks are visible, but they are separated by the nucleus, strongly suggesting that each stack operates as an independent trafficking device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaleforming algae can serve as a "reality check" for models of Golgi traffic (Becker et al 1995). Figure 6A shows a thin-section electron micrograph of S. dubia (Perasso et al 2000). Two Golgi stacks are visible, but they are separated by the nucleus, strongly suggesting that each stack operates as an independent trafficking device.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar, 1.0 mm. (Panel A adapted from Perasso et al [2000] and reprinted with permission from Springer #2000.) (B) An electron tomographic slice of a single S. dubia Golgi stack next to a transitional ER site (tER).…”
Section: Discussionmentioning
confidence: 99%
“…The data by Becker et al (1995) was presented not in the original paper but in a review. Moreover, it was then shown that this experimental model was incorrect (Perasso et al, 2000). The diameter of pre-chylomicrons is greater that the diameter of the internal volume of COPI-dependent vesicles.…”
Section: Intra-golgi Transportmentioning
confidence: 99%
“…At the end of the diastolic phase, the SR is disconnected from the large round CV. Membrane structures representing collapsed CVs have not been reported in S. dubia (Melkonian and Preisig 1986;Perasso et al 2000;Becker and Hickisch 2005).…”
Section: Scherffelia Dubiamentioning
confidence: 88%